2017
DOI: 10.19082/4461
|View full text |Cite
|
Sign up to set email alerts
|

The effect of motivational interviewing-based intervention using self-determination theory on promotion of physical activity among women in reproductive age: A randomized clinical trial

Abstract: BackgroundPhysical activity (PA) prevents chronic diseases. Self-determination theory (SDT) provides a useful framework to understand the nature of motivational interviewing (MI).ObjectiveThis study aimed to determine the effect of MI-based intervention using SDT on the promotion of PA among women in reproductive age.MethodsSeventy women in reproductive age were selected by clustering sampling method for this randomized controlled trial. The questionnaire included the variables of physical fitness test, SDT, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Our review indicated that MI is a powerful intervention to improve autonomous motivation for PA 27,33,35,36 and to reduce amotivation for PA. 27,28,36 Furthermore, these studies indicate that the delivery of the intervention can vary from telephone, 28 to internet, 31,34,37,38 and to one-on-one in-person coaching 32,36 and can still be effective in impacting motivation and PA, regardless of the delivery method.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Our review indicated that MI is a powerful intervention to improve autonomous motivation for PA 27,33,35,36 and to reduce amotivation for PA. 27,28,36 Furthermore, these studies indicate that the delivery of the intervention can vary from telephone, 28 to internet, 31,34,37,38 and to one-on-one in-person coaching 32,36 and can still be effective in impacting motivation and PA, regardless of the delivery method.…”
Section: Resultsmentioning
confidence: 95%
“…In 6 of the included studies, increases in objectively measured or self-reported PA were seen. 27 -32 Other health-related improvements included increases in cardiorespiratory fitness, 27,33,34 decreases in body mass index, 27,28,34 and decreases in systolic blood pressure and non-high-density lipoprotein (HDL) cholesterol. 33…”
Section: Resultsmentioning
confidence: 99%
“…The first group was given educational sessions with MI and pamphlets on PA significance while the other group received only educational sessions. Following a 4-month period after the intervention, the group with MI showed an increase in PAL, internal motivation, perceived competences, autonomy and satisfaction [24]. MI turned out to be helpful in the study of 80 females and males aged 40-65 years old in Australia who took part in a 4-month intervention aimed at introducing new habits of PA in order to fight against sedentary lifestyle.…”
Section: In Physical Activitymentioning
confidence: 96%
“…This theory tries to explain how the interplay between intrinsic and extrinsic factors could sustain individuals’ passions and their efforts to reach personal aspirations. A special focus of the theory is on sociocultural factors that could facilitate or undermine the individuals’ sense of autonomy, competence and relatedness, which were argued to be fundamental in maintaining motivation and performance 5,8,12. Perceived support for autonomy, self-care competence and psychological relatedness based on the theory are crucial for optimal functioning of a patient in accordance with the prescribed medications or behavioral pattern 5,79,1214…”
Section: Introductionmentioning
confidence: 99%
“…The Health Care Climate Questionnaire (HCCQ) was developed by Williams et al17 and measures the perceived needs of patients and extent of HCPs' support with regard to independence and success in motivating patients to accept greater responsibility for their own health 12,18–20…”
Section: Introductionmentioning
confidence: 99%